Penyuluhan Peningkatan Pemahaman Masyarakat terhadap Beyond Use Date Sediaan Obat pada Swamedikasi Secara Daring - Fernanda, M.A. Hanny Ferry; Kusumo, Galuh Gondo (Jurnal Pelayanan dan Pengabdian Masyarakat (Pamas), 2023)
Beyond Use Date (BUD) can be defined as the time limit for a drug product that is safe for use after compounding or after the primary packaging has been opened. In contrast to the Expired Date (ED) or expiration date which is the limit on the use of drugs listed on the drug packaging. This BUD is not listed on the drug packaging so people need to know about this BUD. This BUD really determines the time limit for a drug product that is still of good quality and is in a stable condition. Ideally, the BUD is determined based on the results of the drug product stability test and is listed on the packaging. However, when doing self-medication or self-medication, people usually only use the expiration date as a reference for the safety of drug use. Therefore, there is a need for community service activities to provide education to the community about knowledge of drug damage after the packaging is opened and before ED. The purpose of this activity is to increase public knowledge about the safety of pharmaceutical preparations as long as they are stored with a time limit after the packaging is opened. This activity was carried out online through the zoom meeting application on Saturday, April 10, 2021. The results of this activity provided information that the public could understand the Beyond Use Date material on the use of self-medication drugs properly. Keywords : Beyond Use Date, Expired Date, Self Medication